Li-fi: current state, progress and forward projection - Rodríguez Erazo, David Andres; Torres Guzmán, Geral Alexander (Ingeniería Solidaria, 2021)
Problem: The increase in wireless devices connected to the internet, saturation of the electromagnetic spectrum used by wireless technologies based on current radio frequencies (Wi-Fi, Bluetooth, ZigBee, among others), new requirements for bandwidth, speeds and energy efficiency for the new generations of telecommunications are the cause of the birth of Li-Fi as an alternative and / or complementary technology of wireless telecommunication that is based on the visible light spectrum. Objective: The objective of this research is to expose the development of Li-Fi technology in the field of telecommunications, covering it in three main aspects such as the current state of technology, recent advances, and future projections. Methodology: Different types of bibliographic sources were used, including research and opinion articles, marketing studies, forums, books, conferences, among others with a publication date of 2012 onwards (some exceptions are found in the references); taking as selection criteria title, authors, date of publication, abstract, results and / or conclusions in relation to the research guidelines (Current Status, Advances and Future Projection of Li-Fi technology) Conclusion: The literature review article manages to highlight the importance of Li-Fi in the new generations of telecommunications of the future and its complementarity with current networks, optimally contextualizing the technology, exposing its advantages and recent advances in technical and commercial aspects as well like its disadvantages and points. weaknesses that should be addressed in the development of this technology in the future